Simulation of Formation of Icosahedral Structure in Solid-Liquid-Solid Phase Change Using Molecular Dynamics Methods - Nikodemus Umbu Janga Hauwali; Artoto Arkundato; Lutfi Rohman (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2016)
It has successfully conducted research to study the structure of the icosahedral formation in the event of change of the solid phase - liquid-solid using molecular dynamics method . The result showed that the percentage of the maximum icosahedral structure is obtained when the simulation is run at the start of the cooling temperature of 2875 K at a rate of temperature decrease of 0.064 K /step and at the beginning of the cooling temperature of 3000 K at a rate of temperature decrease 0.12 K/step. While icosahedral minimum percentage obtained when the simulation is run at a temperature of 2750 K with the initial cooling rate of temperature decrease of 0.069 K/step. Based on these results we can conclude that there is a relationship between the initial temperature of the cooling and the rate of temperature decrease of the icosahedral structure is formed. Keywords: Icosahedral, phase change, molecular dynamics